2009
DOI: 10.1097/rlu.0b013e3181b53a46
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Silent Myocardial Ischemia During the Staging of HIV-Associated Lymphoma With FDG PET/CT

Abstract: Fasting 18F fluoro-deoxy-glucose positron emission tomography examinations are routinely performed for the staging of HIV-associated lymphomas. In addition to possible comorbidity factors, the chronic inflammation that occurs in HIV-infected patients together with the metabolic side effects of antiretroviral therapy increases the risk for coronary artery disease. Moreover, HIV-infected patients are likely to develop polyneuropathies due to the viral infection or to the side effects of long-term protease or nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Garcia et al showed a further correlation between myocardial vessel calcifications and the frequency of focal 18 FDG myocardial uptake [26]. Finding of unknown ischemia on an MPS performed after finding a focal 18 FDG uptake has been described in a case report [27].…”
Section: Discussionmentioning
confidence: 90%
“…Garcia et al showed a further correlation between myocardial vessel calcifications and the frequency of focal 18 FDG myocardial uptake [26]. Finding of unknown ischemia on an MPS performed after finding a focal 18 FDG uptake has been described in a case report [27].…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, all but one of the myocardial scintigraphic studies in HIV-infected patients have investigated only endothelial or vasomotor function [37,38] or have investigated a single clinical case [39]. The only clinical study of myocardial perfusion using gated SPECT in HIVinfected patients under highly active antiretroviral therapy is that of Catzin-Kuhlmann et al and the finding was negative [23].…”
Section: Discussionmentioning
confidence: 99%
“…[1] FDG PET/CT study has evolved not only as a tool to improve our understanding of the pathogenesis of HIV-1 infection, but also in diagnosis, staging, restaging, and monitoring therapeutic response in the opportunistic infections and malignancies. [2789101112] Furthermore, increased FDG uptake in subcutaneous adipose tissue has been demonstrated in diagnosed cases of LD. [213] The awareness of this uptake pattern is important when evaluating FDG PET in patients undergoing HAART.…”
Section: Discussionmentioning
confidence: 99%